Insurance Market in the Light of Covid-19 Pandemic - Ratowska-Dziobiak, Eleonora (Journal of Finance and Financial Law, 2022)
The COVID-19 pandemic has been compared to world wars or other tragic events in terms of the death toll it has taken and huge economic losses it has caused. It is not a finished process, so it is difficult to predict the scale of its impact. According to IMF estimates, the contraction of the world economy will be much greater than in the years of the financial crisis of 2008–2009. The negative effects in different countries may depend on the severity and extent of the applied lock-down or interventions undertaken by governments. Changes taking place in various sectors of the economy are of a different nature. The effects of the pandemic can be also seen in the insurance segment. The aim of this article is to find answers to the following research questions: To what extent did the COVID-19 pandemic affect the situation on the insurance market? In which areas are its consequences particularly visible? What kind of opportunities and threats does the pandemic bring from the perspective of the insurance market? Methodology. The analysis used available scientific publications, reports prepared by the Polish Financial Supervision Authority, Polish Insurance Association and entities conducting brokerage activities or selected consulting companies. The result of the research. In a few days, in March 2020, a real revolution took place on the insurance market. The insurers faced the need to introduce completely remote customer service. They also had to launch new tools, which in many cases were still in the testing phase and which they did not have the opportunity to use on a large scale. With the onset of the pandemic, they were quickly implemented. It was related to additional funds, huge commitment and discipline of all employees, liquidators, agents, sales departments, and administration. Consequent on this, clients gained full access to all services and insurance products, without leaving home. On the other hand, pandemic has led to the significant changes within the demand for the insurance services and customers’ expectations, but also to growing scale of damages and compensation paid to the clients leading to the higher insurance premiums.